Thyroid hormone negatively regulates tumorigenesis through suppression of BC200. Issue 12 (December 2018) - Lin, Yang-Hsiang; Wu, Meng-Han; Huang, Ya-Hui; Yeh, Chau-Ting; Chi, Hsiang-Cheng; Tsai, Chung-Ying; Chuang, Wen-Yu; Yu, Chia-Jung; Chung, I-Hsiao; Chen, Ching-Ying; Lin, Kwang-Huei
Abstract : Thyroid hormone (T3 ) and its receptor (TR) are involved in cancer progression. While deregulation of long non-coding RNA (lncRNA) expression has been detected in many tumor types, the mechanisms underlying specific involvement of lncRNAs in tumorigenicity remain unclear. Experiments from the current study revealed negative regulation of BC200 expression by T3 /TR. BC200 was highly expressed in hepatocellular carcinoma (HCC) and effective as an independent prognostic marker. BC200 promoted cell growth and tumor sphere formation, which was mediated via regulation of cell cycle-related genes and stemness markers. Moreover, BC200 protected cyclin E2 mRNA from degradation. Cell growth ability was repressed by T3, but partially enhanced upon BC200 overexpression. Mechanistically, BC200 directly interacted with cyclin E2 and promoted CDK2–cyclin E2 complex formation. Upregulation of cell cycle-related genes in hepatoma samples was positively correlated with BC200 expression. Our collective findings support the utility of a potential therapeutic strategy involving targeting of BC200 for the treatment of HCC.